2008
DOI: 10.3727/096368908786516819
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-Induced Increase in Survival and Migration of Human Neural Progenitor Cells Releasing GDNF

Abstract: The use of human neural progenitor cells (hNPC) has been proposed to provide neuronal replacement or astrocytes delivering growth factors for brain disorders such as Parkinson's and Huntington's disease. Success in such studies likely requires migration from the site of transplantation and integration into host tissue in the face of ongoing damage. In the current study, hNPC modified to release glial cell line derived neurotrophic factor (hNPC GDNF ) were transplanted into either intact or lesioned animals. GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
2
43
1
Order By: Relevance
“…In animal studies, cell survival and migration can be assessed using post-mortem histological analyses (Tang, Shah et al 2003, Behrstock, Ebert et al 2008, Riley, Federici et al 2009). However, a method of in vivo noninvasive, longitudinal cell tracking in clinical settings would be invaluable, allowing scientists to understand cell dynamics in single subjects as well as cohorts and adapt stem/progenitor cell therapies for further studies.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, cell survival and migration can be assessed using post-mortem histological analyses (Tang, Shah et al 2003, Behrstock, Ebert et al 2008, Riley, Federici et al 2009). However, a method of in vivo noninvasive, longitudinal cell tracking in clinical settings would be invaluable, allowing scientists to understand cell dynamics in single subjects as well as cohorts and adapt stem/progenitor cell therapies for further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated an increased expression of AQP3 in skin carcinoma, increased AQP4 expression in glioblastoma and increased AQP5 expression in pancreatic and colon cancer (21)(22)(23)(24). Cell migration is affected by numerous factors; it is time-dependent (25), significantly enhanced by collagen IV in embryonic stem cells (26), and it has been observed that even a lesion can induce an increase in the migration of human neural progenitor cells (27). The findings from this study demonstrate that AQP5 knockdown reduced the migration of EC cells, suggesting that AQP5 is involved in the development of EC.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, spinal cord-derived stem cells (59) and cortical-derived hNPCs (41) have been shown to ameliorate the symptoms of ALS in a transgenic rat model of the disease, while a recent phase I clinical trial validated the safety of spinal cord-derived human neural stem cell delivery to the spinal cord for treatment of ALS (45). These studies, along with a number of others, support the use of hNPCs for therapy of neurodegenerative disorders (2,4,29). …”
Section: Introductionmentioning
confidence: 53%
“…The hNPC G010 line was prepared from the male fetal cortex and expanded using a previously described method (51). These cells have been characterized over several decades (42,52) and have shown to survive and have beneficial effects in multiple degenerative diseases (4,22,49). The cells were grown as free-floating cell clusters, termed neurospheres, in medium which contained Dulbecco’s modified Eagle medium (DMEM; Sigma-Aldrich, St. Louis, MO, USA) and Ham’s F12 (Sigma-Aldrich) (7:3), and penicillin/streptomycin/amphotericin B (PSA, 1% v/v; Life Technologies, Grand Island, NY, USA), supplemented with B27 (2% v/v; Life Technologies), epidermal growth factor (EGF, 100 ng/ml; Millipore Corp., Billerica, MA, USA), fibroblast growth factor-2 (FGF-2, 20 ng/ml; Millipore) and heparin (5 Îźg/ml; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%